Penerapan Digital Marketing dalam Meningkatkan Penjualan UMKM “Rumah Mutiara Cake” di Kecamatan Bengkalis - Silalahi, Anita Rahayu; Bustami Bustami; Nofiar.Am, Andri; Hadi, Larbiel; Hafid, Burhan (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The implementation of digital marketing through social media has proven effective in increasing product sales and visibility, particularly for small businesses such as Rumah Mutiara Cake MSMEs. Digital marketing strategies not only focus on boosting sales but also play a key role in building an active community, expanding market reach, and strengthening relationships between entrepreneurs and consumers. This project aims to explore the implementation of digital marketing at Rumah Mutiara Cake MSMEs in Bengkalis District, develop an appropriate digital marketing framework, conduct a SWOT analysis to identify strengths, weaknesses, opportunities, and threats, and examine the challenges and solutions encountered during the digital marketing process. The project was carried out through several stages, including preparation, implementation, completion, and reporting, located at Jalan Kelapapati Darat, Bengkalis. The results indicate that implementing digital marketing strategies through social media, particularly Instagram and TikTok, has significantly improved the number of followers, customer engagement, and product sales within one month. This demonstrates that optimal use of social media can serve as an effective tool to support the sustainability and growth of MSMEs in the digital era.